2023
DOI: 10.14309/ajg.0000000000002345
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of Financial Burden, Distress, and Toxicity of Inflammatory Bowel Diseases in the United States

Olivia Kahn-Boesel,
Sandhya Cautha,
Nneka N. Ufere
et al.

Abstract: INTRODUCTION: Inflammatory bowel diseases (IBD) affect >3 million Americans and are associated with tremendous economic burden. Direct patient-level financial impacts, financial distress, and financial toxicity are less well understood. We aimed to summarize the literature on patient-level financial burden, distress, and toxicity associated with IBD in the United States. METHODS:We conducted a literature search of US studies from 2002 to 2022 focused on direct/indirect costs, financial distress, and toxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…ability to afford out of pocket costs, access to health insurance, being able to have transportation to medical visits, ability to take off work to attend medical appointments, etc.) have demonstrated that, despite limited research, costs of having IBD are high, which is impactful for families and provides a salient context of risk to be considered ( 47 , 48 ).…”
Section: Dimension 1: Contexts Of Risk Exposurementioning
confidence: 99%
“…ability to afford out of pocket costs, access to health insurance, being able to have transportation to medical visits, ability to take off work to attend medical appointments, etc.) have demonstrated that, despite limited research, costs of having IBD are high, which is impactful for families and provides a salient context of risk to be considered ( 47 , 48 ).…”
Section: Dimension 1: Contexts Of Risk Exposurementioning
confidence: 99%
“…The prevalence of inflammatory bowel disease (IBD) is increasing in most countries and is reaching 1% in high‐incidence areas 1 . This not only increases the economic burden of IBD care but also places additional strains on healthcare professionals taking care of IBD patients 2 . This has naturally led to a gradual shift of conventional medical management tasks from physicians to highly specialised IBD nurses 3 .…”
mentioning
confidence: 99%